UJI AKTIVITAS EKSTRAK ETANOL KOMBINASI DAUN PANDAN WANGI DAN DAUN JAMBU BIJI TERHADAP Shigella dysenteriae - Oom Komala; Durrotun Nafisah Abd.Nf; Novi Fajar Utami (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2021)
Dysentery can be treated using Pandanus amarylifolius leaves and Psidium guajava leaves. This study aimed to determine the activity of the combination of 96% ethanol extract of P. amarylifolius leaves and P. guajava leaves in inhibiting the growth of Shigella dysenteriae bacteria. Methods. Extraction of P. amarylifolius leaves and P. guajava leaves respectively by using the maceration method with 96% ethanol solvent. For the combination treatment, each of these extracts was combined. Each extract obtained was tested for minimum inhibitory concentration (MIC). The MIC value of P. amarylifolius leaf extract was obtained at a concentration of 30% and P. guajava leaf extract was obtained at a concentration of 40%. Inhibitory width test (IWT) by disc diffusion method was carried out on single extracts and combination extracts, with treatment concentrations of 30% single extract of P. amarylifolius leaf (K1), 40% single extract of P. guajava leaf (K2), combination 1 (P. amarylifolius leaf). 30%+ P. guajava leaf 40%) (K3), combination 2 (35% P. amarylifolius leaf + 40% P. guajava leaf) (K4), combination 3 (40% P. amarylifolius leaf + 40% P. guajava leaf) (K5). The width of the inhibition of the research results of the treatment against S. dysenteriae were analyzed using a completely randomized design and Duncan's test. The results showed that the combination of P. amarylifolius leaf extract and P. guajava leaf was more effective in inhibiting the growth of S. dysenteriae bacteria. The combination of P. amarylifolius leaf extract and P. guajava leaf extract that was most effective in inhibiting the growth of S. dysenteriae bacteria was combination 3 (40% P. amarylifolius leaf extract + 40% P. guajava leaf extract) with an average inhibitory width of 5.625 mm.Â Keywords: Combination, P. amarylifolius Leaves, P.guajava Leaves, S. dysenteriae